Comparison of Dynamic Stability Response of A SMIB with PI and Fuzzy Controlled DPFC - Budi Srinivasarao; G. Sreenivasan; Swathi Sharma (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
Consumer utilities are non –linear in nature. This injects increased flow of current and reduced voltage with distortions which cause adverse effect on the stability of consumer utilities. To overcome this problem we are using a modern Flexible Alternating Current Transmission System controller i.e. distributed power flow controller (DPFC). This controller is similar to UPFC, which can be installed in a transmission line between the two electrical areas. In DPFC, instead of the common Dc link capacitor three single phase converters are used. In this paper we are concentrating on system stability (oscillation damping). For analyzing the stability of a single machine infinite bus system (SMIB) we have used PI controlled Distributed Power Flow Controller (DPFC) and Fuzzy controlled DPFC. All these models are simulated using MATLAB/SIMULINK. Simulation results shows Fuzzy controlled DPFC are better than PI controlled DPFC. The significance of the results are better stability and constant power supply.